2021
DOI: 10.1111/jog.15108
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and hematological parameters associated with disease severity in COVID‐19 positive pregnant women undergoing cesarean section: A single‐center experience

Abstract: Aim: The study aimed to describe clinical characteristics and outcomes of pregnant women with COVID-19 undergoing cesarean section, and evaluated the association of blood values at admission with severe COVID-19 disease in this group of patients. Method: We retrospectively analyzed the clinical data of 110 patients infected with COVID-19 who underwent cesarean section at Adana City Education and Research Hospital in Turkey. The COVID-19 severity of the patients was classified as either severe or nonsevere dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
(54 reference statements)
1
8
0
Order By: Relevance
“…Raised alanine and aspartate transaminase was a significant finding in the present study. A similar result was noted in a retrospective study from Turkey that included 110 women [11]. They concluded the predictor value of LDH levels to be higher for severe infection.…”
Section: Discussionsupporting
confidence: 81%
“…Raised alanine and aspartate transaminase was a significant finding in the present study. A similar result was noted in a retrospective study from Turkey that included 110 women [11]. They concluded the predictor value of LDH levels to be higher for severe infection.…”
Section: Discussionsupporting
confidence: 81%
“…One study analyzing exclusively pregnant women from Turkey observed a higher frequency of the O blood group in women who developed severe COVID. However, this study should be taken cautiously since the number of women included was relatively small [ 22 ]. In a study conducted in Spain, including exclusively pregnant women, the proportion of asymptomatic women was significantly higher in non-O groups when compared with the O group.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies concentrated on the severity of COVID-19 and its effect on the incidence of pre-eclampsia. Arslan et al [ 38 ] observed pre-eclampsia in 11 out of 110 pregnant patients with COVID-19, with a higher percentage in non-severe patients ( p -value = 0.09). A prospective observational study, conducted by Mendoza et al [ 39 ], studied 34 cases of non-severe and eight cases of severe COVID-19 pregnant women.…”
Section: Resultsmentioning
confidence: 99%